Bioretention systems for stormwater management: overview and design criteria (Research, Society and Development, 2020)
Rampant urbanization alters the hydrological cycle by intense waterproofing and a consequent reduction in rainwater infiltration. The need to restore the natural conditions of urban basins for the proper management of runoff is evident. This paper describes the state of the art about bioretention systems (rain gardens, bioretention tree pits, bioretention swale and anaerobic bioretention system). Such systems represent alternatives to traditional urban drainage, making possible the recovery of pre-urbanization hydrological conditions. Based on broad bibliographical research, the performance of these structures proves their efficiency regarding the quantitative and qualitative aspects of runoff. However, the lack of information in countries with different weather conditions from those in which research was carried out demonstrates the need to propose general design criteria for applying bioretention systems effectively. Therefore, this paper presents, in general terms, the main design criteria of bioretention systems serving as a guide for future work.